Moderasi Kepemilikan Institusional pada Determinan Pengungkapan Corporate Social Responsibility Perusahaan Sektor Energi (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2024)
The running of a company's operations is, of course, related to the impact on social and environmental aspects, meaning that the operational activities of a business entity not only have an impact on the company itself but also the environment and surrounding community, such as relations with stakeholders in the community, human resources, and natural resources. This research aims to determine the moderating interaction of Institutional Ownership in the influence of Tax Aggressiveness, Profitability, and Media Exposureon Corporate Social Responsibility disclosure in Energy Sector Companies Listed on the BEI in 2018-2024. This research uses a quantitative research approach. The data in this research is secondary data. The sampling technique used purposive sampling, resulting in a sample of 13 energy sector companies. The analysis tool used is eviews13. The research results show that the Tax Aggressiveness variable has no effect on Corporate Social Responsibility disclosure, the Profitability variable has an effect on Corporate Social Responsibility disclosure, and Media Exposurehas an effect on Corporate Social Responsibility disclosure. The Institutional Ownership variable can moderate the influence of Tax Aggressiveness and Profitability on Corporate Social Responsibility disclosure. Meanwhile, the Institutional Ownership variable cannot moderate the influence of Media Exposureon disclosure of Corporate Social Responsibility.